In Quest of the Craft Economic Modeling for the 21st Century - Meade, Douglas S. (Studi e saggi, 2015)
INFORUM is a research project started more than forty five years ago by Clopper Almon. The focus is on the development of dynamic, interindustry, macroeconometric models to forecast the economy in the long run. Over the last 30 years, the Inforum approach to model building has been shared by economists in many different countries. Researchers have focused much of their efforts to developing a linked system of international interindustry models with a consistent methodology. A world-wide network of research associates use similar methods and a common software obtaining comparable results to produce studies of common interest to the group. Inforum partners have shared their research in an annual conference since 1993. The XXII Inforum World Conference was held in Alexandria, Virginia in September 2014 and this book contains a selection of papers presented during the sessions. All these contributions share an empirical and pragmatic orientation that is very useful for policymakers, business, and applied economists. Some papers are devoted to specific topics (productivity, energy, international trade, demographic changes) and some others are oriented to model building and simulations.